Relationship between respiratory systems` parameters and result in swimming - Jakubovskis, G.; Zuša, A.; Solovjova, J. (LASE Journal of Sport Science, 2022)
The efficiency of swimming time could have a close relationship with swimming technique as well, as respiratory system parameters. This research aimed to evaluate the relationship between respiratory system parameters and result in a 100m distance in 44 competitive swimmers (males n=28, females n=16 ). Swimmers were divided in two groups: young swimmers (males n=14, ages 16.5±0.3 years, body mass 74.3±7.5kg, height 183.9±3.5cm; females n=11, ages 16.5±0.3 years, body mass 60.2±7.2kg, height 170.3±7.1cm) and adults athletes (males n=14, ages 21.2±3.3 years, body mass 83.2±10.0kg, height 187.8±7.2cm; females n=5, ages 21.8±4.5 years, body mass 65.7±7.5kg, height 174.20±7.29cm). Outcome measures were 100m distance time and respiratory parameters. Results. The average competition results in the men's group were 628 FINA points, in the women's group 592 FINA points, in the group of 16-17-year-old athletes men's group is 588 FINA points, in the women's group 574 FINA points. Respiratory system indicators: men`s group FVC - 6.47±0.53l., PIF - 8.55±1.34l/s, PEF - 9.95±0.40l/s, in the women's group FVC - 4.86±0.67l., PIF - 6.15±0.67 l/s, PEF 7.57±0.43 l/s. Conclusions. A strong relationship was found between 100m competitive swimming time and peak inspiratory flow in the adult male swimmer group (r=.75). As well as a relationship between the volume of fortified inhale per second and a competitive result in a group of 16-17 years old was found during the research (r= .55).